PENGARUH PESAN DAKWAN PROGRAM “KAJIAN BERSAMA USTADZ” RADIO HIDAYAH 103,4 FM TERHADAP PENGETAHUAN ILMU AGAM ISLAM PADA MASYARAKAT KOTA PEKANBARU - Diena Nurul Haq; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Da'wah to God is the most noble and principal position for a servant, then it will not happen except with science. Da'wah is built on three basic principles, namely, Akidah, Syariat and Akhlak. The mass media conveys its messages to a wide and unlimited audience. Basically mass communication reveals the reaction resulted from the stimulus which in this case is given by the mass media. There is a close connection between media messages with the reaction or response of the audience. The S-R theory suggests that media messages containing the stimulus produce different responses from the audience. The purpose of this study is to find out how much influence the message preaching program "study together ustadz" Radio Hidayah against knowledge of Islamic religion in the city of Pekanbaru.The method used in this research is descriptive quantitative method, with research population is Pekanbaru city people who make calls and text messages with Radio Hidayah as respondents. Selection of respondents as the object of research related to how big the influence of Radio Hidayah as a message channel of da'wah by using Purposive Sampling technique from Unknown Population calculation formula hence this research get 96 respondent. Methods of data collection by field research (field research) by distributing questionnaires, questionnaires and data library research. Data processing technique used is data processing with the help of software SPSS 16 and using likert scale.The result of simple linear regression, obtained by regression coefficient value in this research is Y = 2,245 + 0,377 X. Constant value equal to 2,245 mean that if message of da'wah is zero value of religion knowledge equal to 2,245 unit. coefficient of religious knowledge variable of 0.377. Based on the calculation of statistics obtained, then the hypothesis for this research that is there Influence Program "Study together Ustadz" Radio Hidayah 103.4 FM to Knowledge of Islamic Science on the city of Pekanbaru then Ha accepted Ho is rejected. The influence of the message of dakwah program of "study with ustadz" radio hidayah 103,4 fm to the knowledge of Islamic religion in society Pekanbaru city equal to 80,4%. This means that the influence of the message of dakwah of "study with ustadz" program of 80.4% towards the knowledge of Islamic Science is categorized as having a very strong influence.Keywords: Radio, Program, Message Of Da’wah And Knowledge Of Islamic